Respuesta :
Answer:
The y-intercept of g(x) is equal to 2 times the y-intercept of f(x)
Step-by-step explanation:
The functions f(x) and g(x) are described using the following equation and table
x : -1 0 1 2
g(x) : -4 6 8 10
f(x) : 2.94 3 3.06 3.12
We need to compare the y-intercept of f(x) and g(x)
As we know the y-intercept of any function when x=0.
First we find the y-intercept of f(x) and g(x), f(0) and g(0)
y-intercept of g(x), g(0) = 6
y-intercept of f(x), f(0) = 3
6 is 2 times of 3.
Therefore, The y-intercept of g(x) is equal to 2 times the y-intercept of f(x)
Answer:
A. The y-intercept of f(x) is equal to the y-intercept of g(x)
Step-by-step explanation:
First, take a look at f(x)
f(x) = -3(1.02) x
Here we see that the y - intercept is -3
the table represents g(x)
remember when x = 0 that is where the y-intercept is
in this case x = 0 when y = -3
this means f(x) and g(x) have the same y - intercept which is -3